High-toughness X60 / X65-grade anti-acid pipeline steel and manufacturing method thereof

By optimizing the chemical composition and microstructure of acid-resistant pipeline steel, the problems of hydrogen-induced cracking and insufficient low-temperature toughness caused by segregation elements in the prior art are solved, and high toughness and excellent acid-resistant properties are achieved, meeting the API 5L standard. Strength and toughness requirements.

CN119220889AActive Publication Date: 2024-12-31BAOSHAN IRON & STEEL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310780899.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The content of easily segregated elements such as C and Nb in existing acid-resistant pipeline steels is high, resulting in increased sensitivity to core segregation and hydrogen-induced cracking, difficult to improve low-temperature toughness, and poor acid-resistant performance.

Method used

By optimizing chemical composition, the C content is controlled at 0.015-0.040%, Mn is between 1.18-1.45%, Nb is between 0.025-0.055%, Ti is between 0.005-0.020%, Cu+Ni+Cr+Mo≤0.80%, and meet specific The sensitivity coefficient of hydrogen-induced cracking Ks is ≤0.23, forming a uniformly refined granular bainite + a small amount of bulk ferrite microstructure, reducing segregation and hard phase structure.

Benefits of technology

It has achieved high toughness and excellent resistance to hydrogen cracking and hydrogen sulfide stress corrosion of X60/X65 grade acid-resistant pipeline steel, and has good low-temperature toughness. Rt0.5 yield strength is 430~570MPa, and tensile strength is 520~690MPa. -49℃ Charpy impact force ≥400J, -35℃ DWTT SA%≥90%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220889A_ABST
    Figure CN119220889A_ABST
Patent Text Reader

Abstract

The high-toughness X60 / X65-grade acid-resistant pipeline steel comprises the following components in percentage by weight: 0.015-0.040% of C, 0.10-0.30% of Si, 1.18-1.45% of Mn, 0 < P < = 0.008%, 0 < S < = 0.0010%, 0.05-0.35% of Cu, 0.05-0.30% of Ni, 0.15-0.30% of Cr, 0.02-0.09% of Mo, 0.025-0.055% of Nb, 0.005-0.020% of Ti, 0.0010-0.0040% of Ca, 0.010-0.040% of Alt, 0 < B < = 0.0004%, 0 < O < = 0.0025%, 0 < N < = 0.0050%, 0 < H < = 0.0002%, 0 < Sn < = 0.0050%, 0 < Sb < = 0.0025%, 0 < Bi < Ca / S > = 2; 0.80% or less of Cu, Ni, Cr and Mo; 0 < N + O + H < = 0.0070%; 0.7 < = (Nb + 27.5 * Ti) / (5C + 27 * N) < = 5.0; the hydrogen induced cracking sensitivity coefficient Ks is less than or equal to 0.23, and Ks is equal to 8.0 C + 24S-Alt-2.3 Nb + 2.8 Ti + 117B + 0.34 Ni-0.30 Mo + 24.5 N-0. 19. The obtained pipeline steel can reach the X60 / X65 strength level, and has good low-temperature toughness and excellent HIC and SSC resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metal materials and their manufacture, and specifically relates to a high-toughness X60 / X65 grade acid-resistant pipeline steel and a manufacturing method thereof. Background Art

[0002] With the continuous development of conventional oil and gas fields, the reserves are constantly decreasing, and the development ratio of H2S-containing acidic oil and gas fields is further increasing, which requires the pipeline to have acid resistance. The designers of different acid-resistant pipeline projects will formulate personalized acid-resistant indicators according to the service conditions of the pipeline, including NACE standard resistance to hydrogen-induced cracking (HIC) performance, resistance to hydrogen sulfide stress corrosion cracking (SSC) performance, and strict low-power rating and flaw detection requirements.

[0003] Chinese patent CN202010552764.7 discloses "a magnesium-containing X65 pipeline steel with excellent acid resistance and production method". The components and weight percentage of the pipeline steel are: C: 0.03-0.05%, Si: 0.17-0.20%, Mn: 0.40-0.70%, Ni: 0.12-0.15%, Cr: 0.45-0.48%, Mo: 0.10-0.15%, Mg: 0.002-0.004%, Nb: 0.06-0.09%, Ti: 0.01-0.02%, P≤0.008%, S≤0.010%, and the rest are Fe and unavoidable impurities. The patent adopts the Mg treatment method for inclusion treatment, and the Mn content is relatively low in composition. Therefore, by adding more Nb, Cr and a certain amount of Mo to ensure strength, the acid-resistant pipeline steel with X65 strength level is obtained. However, the Mg treatment method for inclusions is difficult to control for stable addition, and has poor control effect on inclusions such as MnS, which has an adverse effect on acid resistance and toughness. The obtained acid-resistant pipeline steel has a Charpy impact energy of ≥200J at -20℃ and a DWTT SA% of ≥90% at -15℃.

[0004] Chinese patent CN201510870777.8 discloses "a thick-gauge acid-resistant X60MS hot-rolled coil and its manufacturing method". The composition of the steel plate is as follows by weight percentage: C: 0.050-0.070%, Si: 0.15-0.25%, Mn: 1.35-1.45%, Nb: 0.025-0.045%, Ti: 0.008-0.025%, Mo: 0.06-0.10%, Cr: 0.08-0.18%, Als: 0.015-0.045%, P≤0.015%, S≤0.0015%, N≤0.006%. Since the increase in C content will significantly increase the degree of segregation in the steel, increase the material's anti-HIC sensitivity, and reduce the material's low-temperature toughness to a certain extent, the resulting material has a -40°C Charpy impact energy ≥300J, -30°C DWTT SA%≥85%.

[0005] Chinese patent CN202011197059.6 discloses "A X60 / X65 grade acid-resistant pipeline steel and its preparation method", whose chemical composition and mass percentage are as follows: C: 0.02~0.06%, Si: 0.10~0.20%, Mn≤0.90%, Al: 0.020~0.050%, Nb: 0.060~0.080%, Ti≤0.020%, Cr≤0.30%, Ni≤0.20%, Cu≤0.40%, P≤0.012%, S≤0.002%, N≤0.0060%, B≤0.0005%, Mn+Cr≤1.2%, and the rest are iron and unavoidable impurity elements. The patented alloy design adds more Nb (0.060-0.080%). The higher Nb content increases the tendency of Nb-containing particles in the steel to gather in the core, and the probability of HIC cracks appearing in the core of the steel plate increases accordingly.

[0006] From the comparison with the existing patents, it can be found that the existing acid-resistant pipeline steels contain high levels of easily segregated elements such as C and Nb, which can easily lead to segregation and inclusions in the core, increase the material's HIC sensitivity, increase the possibility of hydrogen-induced cracking, and make it difficult to further improve the material's low-temperature toughness. Summary of the invention

[0007] The object of the present invention is to provide a high-toughness X60 / X65 grade acid-resistant pipeline steel and a manufacturing method thereof, wherein the obtained pipeline steel can reach the X60 / X65 strength level and has good low-temperature toughness and excellent HIC and SSC resistance. t0.5 Yield strength 430~570MPa, tensile strength 520~690MPa, yield strength ratio ≤0.92, A50mm elongation ≥30%, hardness HV10≤220, -49℃ Charpy impact energy ≥400J, -35℃ DWTT SA% ≥90%.

[0008] To achieve the above object, the technical solution of the present invention is:

[0009] A high-toughness X60 / X65 grade acid-resistant pipeline steel, the chemical composition weight percentage of which is: C: 0.015-0.040%, Si: 0.10-0.30%, Mn: 1.18-1.45%, 0<P≤0.008%, 0<S≤0.0010%, Cu: 0.05-0.35%, Ni: 0.05-0.30%, Cr: 0.15-0.30%, Mo: 0.02-0.09%, Nb: 0.025-0.055%, Ti: 0.005 ~0.020%、Ca:0.0010~0.0040%、Al:0.010~0.040%、0<B≤0.0004%、0<O≤0.0025%、0<N≤0.0050%、0<H≤0.0002%、0<Sn≤0.0050%、0<Sb≤0.0025%、0<Bi≤0.0030%、0<Pb≤0.0050%、0<As≤0.0030%、the balance includes Fe and unavoidable impurities, and at the same time meets:

[0010] Nb+Ti≤0.07%;

[0011] Ca / S ≥ 2;

[0012] Cu+Ni+Cr+Mo≤0.80%;

[0013] 0<N+O+H≤0.0070%;

[0014] 0.7≤(Nb+27.5*Ti) / (5C+27*N)≤5.0;

[0015] Hydrogen induced cracking sensitivity coefficient Ks≤0.23, Ks=8.0C+24S-Alt-2.3Nb+2.8Ti+117B+0.34Ni-0.30Mo+24.5N-0.19.

[0016] Furthermore, the balance is Fe and other inevitable impurities.

[0017] The microstructure of the pipeline steel of the present invention is uniformly refined granular bainite + a small amount of blocky ferrite, wherein the content of blocky ferrite is 3-10%, the grain size is ≥10, and there is no obvious segregation zone or hard phase structure.

[0018] The R of the pipeline steel of the present invention t0.5Yield strength 430~570MPa, tensile strength 520~690MPa, yield strength ratio ≤0.92, A50mm elongation ≥30%, hardness HV10≤220, -49℃ Charpy impact energy ≥400J, -35℃ DWTT SA% ≥90%.

[0019] In the chemical composition design of the acid-resistant pipeline steel of the present invention:

[0020] C: The most economical strengthening element in steel, which improves the strength of steel through interstitial solid solution strengthening. Increasing the carbon content can greatly improve the hardenability of steel, reduce the amount of other precious alloy additions, and reduce production costs, but the increase in C content is unfavorable to the ductility, toughness, weldability and corrosion resistance of steel, especially prone to aggravate core segregation, and has a significant adverse effect on acid resistance. Therefore, the present invention adopts an ultra-low C design, and its content is controlled at 0.015-0.040%.

[0021] Si: solid solution strengthening element, also a deoxidizing element in steel, but too high a content will have an adverse effect on surface quality and welding performance, and if the Si content exceeds 0.30%, toughness may decrease. Therefore, in the present invention, the Si content is controlled at 0.10-0.30%.

[0022] Mn: It improves the strength of steel by solid solution strengthening. It is the most important and economical strengthening element in steel to compensate for the strength loss caused by the reduction of C content. Mn helps to obtain fine phase transformation products and also helps to control oxygen and sulfur in the steelmaking process. If the Mn content is low, it is difficult to obtain the target strength level, but Mn will also aggravate the center segregation. Therefore, in the present invention, the Mn content is controlled at 1.18-1.45%.

[0023] Cr: It has a certain solid solution strengthening effect and can effectively improve the hardenability of steel. When the Cr content is above 0.10%, it can effectively improve the corrosion resistance of steel and form a relatively dense protective layer on the surface of the steel to protect the matrix. However, when the Cr content in the steel is too high, it is not conducive to the quality of the weld and is prone to form gray spot defects. Therefore, the Cr content in the present invention is controlled at 0.15-0.30%.

[0024] Nb: An important element of low-carbon microalloyed steel. During the hot rolling process, the solid-dissolved Nb strain-induced precipitation forms Nb carbonitrides, which pin the grain boundaries to inhibit the growth of deformed austenite. After controlled rolling and controlled cooling, the deformed austenite is transformed into a fine product with a high dislocation density. After the steel strip is coiled, the solid-dissolved Nb will be dispersed and precipitated in the matrix as the second phase particle NbC, which plays a role in precipitation strengthening. More Nb makes the slab prone to cracks, thereby affecting the surface quality, and also deteriorates the welding performance. Therefore, the Nb content in the present invention is controlled at 0.025-0.055%.

[0025] Ti: a good deoxidizing and degassing agent and an effective element for fixing nitrogen and carbon. The undissolved carbonitrides of Ti can prevent the growth of austenite grains when the steel is heated. The TiN and TiC precipitated during rough rolling in the high-temperature austenite region can effectively inhibit the growth of austenite grains and refine the grains. At the same time, they can also increase the solid solubility of Nb and reduce the microcrack sensitivity of Nb-containing steel. It is generally added in combination with Nb. In addition, the precipitation during the welding process can also inhibit the growth of high-temperature grains and improve the welding performance. Therefore, the Ti content in the present invention is controlled at 0.005-0.020%.

[0026] Nb+Ti: The addition of more Nb and Ti will easily lead to the aggregation of coarser Nb / Ti-containing particles in the steel plate, and easily form long strip-shaped segregation distributed along the rolling direction in the core. It is a hard phase with higher hardness than the matrix, which increases the hydrogen-induced cracking sensitivity of the structure and easily causes hydrogen to pin around it and no longer diffuse. Therefore, it is easy to become a hydrogen aggregation site and also easy to become the starting point of hydrogen-induced cracking, which significantly increases the HIC cracking tendency of the core and deteriorates the acid resistance of the material. Therefore, in the present invention, Nb+Ti is controlled to be ≤0.07%.

[0027] In addition, TiN and NbC are important second phases in steel, which have an important influence on strength and toughness. When (Nb+27.5*Ti) / (5C+27*N)>5, the second phase particles are relatively coarse and unevenly distributed, and are easy to gather at the core segregation, which is easy to cause stress concentration and induce brittle fracture, resulting in a sharp decrease in the low-temperature toughness of the sample, significantly reducing the toughness of the parent material and the hot zone of the weld, and also becoming a hard phase that causes hydrogen-induced cracking. When (Nb+27.5*Ti) / (5C+27*N)<0.7, the number of precipitated phases is small, and the size is too small, which is easy to dissolve into the parent material again, and the grain boundary pinning effect is weak, which is also unfavorable to toughness. Therefore, in the present invention, 0.7≤(Nb+27.5*Ti) / (5C+27*N)≤5.0 is controlled.

[0028] Mo: A strong hardenability element, which significantly delays the ferrite phase transformation, inhibits the formation of ferrite and pearlite, and can effectively promote the bainite transformation to strengthen the matrix and obtain a finer structure. A certain amount of Mo has obvious benefits for improving the material structure and properties, but when the Mo content is too high, the plasticity of the steel is reduced, and the cost of Mo is high. Therefore, in the present invention, the Mo content is controlled at a relatively low level of 0.02 to 0.09%.

[0029] Cu and Ni: can improve the strength of steel through solid solution strengthening and improve the atmospheric corrosion resistance of steel, but a high content will cause hot cracks in the steel plate, while Ni can refine the grains and improve the hot brittleness easily caused by Cu in steel, which is significantly helpful for improving low-temperature toughness. Therefore, in the present invention, the Cu content is controlled at 0.05-0.35%, and the Ni content is controlled at 0.05-0.30%.

[0030] Cu+Ni+Cr+Mo: The addition of Cu, Ni, Cr, and Mo elements will increase the production cost, and if the content of Cu, Ni, Cr, and Mo exceeds a certain range, the performance of the steel will be affected, and the hot brittleness tendency of the material will be increased. At the same time, it will promote the formation of MA particles, increase the proportion of hard phases in the steel, and easily become a hydrogen trap, resulting in a series of problems such as hydrogen embrittlement and brittle phases, thereby reducing the HIC resistance and low-temperature toughness. In order to ensure the comprehensive properties of steel such as strength and toughness, and to ensure the controllability of production costs. In the present invention, Cu+Ni+Cr+Mo is controlled to be ≤0.80%.

[0031] S, P: The main impurity elements in steel. Phosphorus easily causes cold brittleness of steel, and sulfur easily causes hot brittleness, which leads to unstable performance of steel. Especially with the increase of S content, the increase of MnS inclusions will significantly increase the sensitivity of hydrogen-induced cracking in steel and reduce acid resistance. The content of phosphorus and sulfur in steel should be reduced as much as possible. Therefore, in the present invention, S is controlled to be ≤0.0010% and P is ≤0.0080%.

[0032] Ca: Ca treatment can control the morphology of sulfides, improve the anisotropy of steel plates, and increase low-temperature toughness; in addition, when the S content is high, ensuring an appropriate Ca / S ratio ensures the material's HIC resistance, but too high a Ca content can easily lead to an increase in inclusions such as CaO in the steel. In the present invention, the Ca content is controlled at 0.0010-0.0040%, and Ca / S is controlled to be ≥2.

[0033] Al: Al is used for deoxidation of steel. A proper amount of Al is also beneficial for grain refinement and improving toughness. However, if the Al content is greater than 0.05%, coarse precipitates may be formed, thereby reducing the acid resistance and low-temperature toughness of the steel. Therefore, the Al content of the present invention is controlled within the range of 0.010-0.040%, and Alt is controlled to be ≤0.08% during the LF / RH process.

[0034] N, O, H: For low-temperature toughness, O, N and H may all cause brittle fracture, especially at low temperatures. The presence of O and N will form O compounds and N compounds, which may aggregate at the grain boundaries, leading to intergranular brittleness. At the same time, H may also penetrate into the grains, causing lattice deformation and hole formation, leading to brittle fracture. Therefore, the low-temperature toughness of steel is related to the content of O, N, and H. Excessive or improper content may lead to brittle fracture. For acid resistance, the effects of O, N and H are also significant. In an acidic environment, O will react with the iron element in the steel to oxidize, causing the steel to lose a certain degree of corrosion resistance. N may form N compounds with the chromium element in the steel, resulting in a decrease in the corrosion resistance of the steel. H will promote stress corrosion cracking of the steel, which will also have a certain impact on the acid resistance of the steel. Therefore, in the present invention, 0<O≤0.0025%, 0<N≤0.0050%, 0<H≤0.0002%, and 0<N+O+H≤0.0070% are controlled.

[0035] B: The main function of B in steel is to increase the hardenability and strength of steel, thereby saving other rare and precious metals, but the addition of B element will have a significant adverse effect on the low-temperature toughness of the material. Therefore, in the present invention, B is controlled to be ≤0.0004%.

[0036] Sn, Sb, Bi, Pb, As: When the content of these elements in steel exceeds a certain limit, the strength of the steel will be reduced, and it is easy to cause serious segregation, forming segregation at the grain boundary, causing brittle cracks to start from the grain boundary and extend along the grain boundary until it is completely broken, significantly reducing the low-temperature toughness of the material; in addition, the presence of a high Sn content in steel will significantly reduce the steel's resistance to HIC hydrogen-induced cracking, because tin will promote the diffusion and aggregation of hydrogen, thereby accelerating the occurrence of hydrogen-induced cracking, and Pb also has a similar effect. Therefore, in the present invention, 0<Sn≤0.0050%, 0<Sb≤0.0025%, 0<Bi≤0.0030%, 0<Pb≤0.0050%, and 0<As≤0.0030% are controlled.

[0037] Hydrogen induced cracking sensitivity coefficient Ks: The HIC resistance is affected by various elements in the steel, such as C and S, which have a significant degree of segregation, Nb and Ti, which participate in the precipitation of the second phase particles, and N, B and other inclusion elements. According to the degree of segregation of each element and the regularity between each element and the HIC resistance, the present invention proposes a hydrogen induced cracking sensitivity coefficient Ks, Ks = 8.0C + 24S-Alt-2.3Nb + 2.8Ti + 117B + 0.34Ni-0.30Mo + 24.5N-0.19 (element unit: wt%). The correlation between the HIC crack length rate CLR and the coefficient Ks is as follows: Figure 1As shown, as Ks increases, the material's hydrogen-induced cracking sensitivity increases, the probability of HIC cracks increases, and the length of the cracks increases. When Ks≤0.23, no cracking occurs in the HIC test. When Ks>0.23, CLR begins to increase significantly. The API 5L SPEC standard requires CLR to be ≤15%, and some engineering projects require CLR≤10% or even stricter. According to the relationship between CLR and Ks, in order to ensure the acid resistance of the material, Ks is controlled to be ≤0.23 in the present invention.

[0038] In general, the present invention adopts the above-designed component system, comprehensively considering the effects of easily segregated elements such as C and S in steel, microalloying elements such as Cu, Ni, Cr, Mo, Nb and Ti, and impurity elements such as N, O, H, B, Sn, Sb, Bi, Pb, As, etc. on the acid resistance and low-temperature toughness of the material, and proposes control requirements for the hydrogen-induced cracking sensitivity coefficient Ks coefficient based on the degree of segregation of each element and its relationship with the HIC resistance performance, so as to improve the acid resistance of the material. On this basis, Nb+Ti≤0.07%, 0.7≤(Nb+27.5*Ti) / (5C+27*N)≤5.0 are controlled, and the influence of second phase particles such as TiN and NbC on the acid resistance and low temperature toughness of the material is mainly considered. At the same time, by adding Cu+Ni+Cr+Mo≤0.80%, the inhibitory effect on the blocky ferrite is reduced, so that a small amount of blocky ferrite (blocky ferrite content 3-10%) is contained in the steel structure to inhibit the generation of cracks, so that the pipeline steel has high strength and acid resistance, and also has good low temperature toughness. The obtained pipeline steel R t0.5 Yield strength 430~570MPa, tensile strength 520~690MPa, yield strength ratio ≤0.92, A50mm elongation ≥30%, hardness HV10≤220, -49℃ Charpy impact energy ≥400J, -35℃ DWTT SA% ≥90%.

[0039] The method for manufacturing the high-toughness X60 / X65 grade acid-resistant pipeline steel of the present invention comprises the following steps:

[0040] 1) Hot metal pretreatment

[0041] Control the S content of hot metal before pretreatment to ≤0.050% and the S content of hot metal entering the furnace to ≤0.0020%;

[0042] 2) Smelting

[0043] According to the above composition, the C content of the steel is controlled to be ≤0.035%, and the S content of the steel is controlled to be ≤0.0080%;

[0044] 3) Refining

[0045] LF and RH refining are used. During LF refining, the stirring time after all alloys are added is controlled to be ≥3min, the RH calcium wire feeding amount is 200-350m, the argon blowing time after the calcium wire feeding is completed is ≥5min, the target Ca content is 10-40ppm, and the Ca / S ratio is controlled to be ≥2;

[0046] 4) Continuous casting

[0047] Continuous casting calming time ≥ 3min, superheat controlled at 10~40℃;

[0048] 5) Reheating

[0049] Heating temperature: 1100-1200℃, holding time: 200-350min;

[0050] 6) Controlled rolling

[0051] Final rolling temperature: 750~900℃;

[0052] 7) Cooling after rolling

[0053] Cooling start temperature: 700-800℃, cooling stop temperature: 300-550℃, cooling rate ≤30℃ / s.

[0054] Preferably, during the smelting process, the bottom blowing flow rate of the converter bottom calming stage is ≥900Nm 3 / h, control the blowing of free oxygen to ≤900ppm.

[0055] In the manufacturing method of the present invention:

[0056] The control of composition and internal quality is crucial to improving the acid resistance and toughness of the material. The increase in the S content in the process and the finished product will increase the precipitation and aggregation of inclusions such as MnS in the steel. The MnS inclusions produced in the core are elongated after rolling and are prone to form gaps after cooling. MnS is one of the most likely locations for HIC to form, which greatly reduces the low-temperature toughness and HIC resistance. In order to ensure that the finished product and the process contain lower S, the present invention needs to control the sulfur content of the molten iron before pretreatment to ≤0.050%, ensure that the S content of the molten iron entering the furnace is ≤0.0020% during the KR treatment, and clean the slag of the molten iron ladle after desulfurization.

[0057] During the smelting process, the bottom blowing flow rate of the converter bottom calming stage is ≥900Nm 3 / h, and the free oxygen is controlled to be ≤900ppm when the blowing is stopped. The increase of C content will aggravate the segregation degree in the steel, so that the inclusions such as MnS are further gathered in the core, and the tendency of hydrogen-induced cracking will be significantly increased. Therefore, the C and S of the ladle steel liquid need to be strictly controlled. In the present invention, the C and S of the ladle steel liquid are controlled to be ≤0.035% and ≤0.0080%.

[0058] In the present invention, according to the pre-desulfurization and pre-deoxidation conditions after the converter, LF adopts aluminum slag for slag deoxidation, and stirs with argon gas at the bottom to achieve the purpose of desulfurization, and the pure stirring time is ≥3min. The target wire feeding amount of RH calcium silicon wire is 200-350m, and after the RH wire feeding is completed, the bottom argon blowing of the ladle with a small flow rate is ≥5min to improve the purity of the molten steel. LF refining treatment further desulfurizes and reduces the S content in the steel. In combination with the RH calcium treatment process, the target Ca is controlled according to 10-40ppm and the Ca / S ratio is controlled ≥2 to modify the inclusions such as MnS and Al2O3 in the steel. By increasing the effective calcium content in the steel, high-melting-point CaS is formed in advance during the solidification of the molten steel, the total amount of MnS generated in this process is suppressed, and all or part of it is modified into CaS. On the other hand, large-particle Al2O3 inclusions are turned into low-melting-point composite inclusions, which promote their floating and purify the internal quality of the molten steel. LF and RH all use low-carbon alloys.

[0059] The continuous casting process adopts full-process protection and constant-speed pouring to ensure that the slab has good internal quality and segregation level. The continuous casting calming time is ≥3 minutes. A higher superheat will increase the degree of segregation, while a too low superheat will prevent inclusions from fully floating, which will have an adverse effect on acid resistance and low-temperature toughness. In the present invention, the superheat is controlled at 10-40°C to control the center segregation, and the low-multiple rating Mannesmann standard is ≤2.

[0060] Slab heating temperature: 1100-1200℃; slab holding time: 200-350min. Sufficient heating temperature and time can ensure that the alloy is fully dissolved and has good uniformity, which is conducive to obtaining uniform structure and plate shape.

[0061] The TMCP process is used for rolling. The final rolling temperature control range is 750-900℃. When the final rolling temperature is too high, the austenite grains are obviously coarsened, which has an adverse effect on the final steel plate structure and performance. When the final rolling temperature is too low, mixed crystal structure is easily generated in the steel, which has an adverse effect on the toughness, plasticity and processing performance of the material.

[0062] After rolling, the DQ+ACC cooling mode is adopted. By limiting the addition level of Mo and Nb elements to a relatively low level, the inhibitory effect on the block ferrite is appropriately reduced, so that the steel undergoes phase transformation under the conditions of the start cooling temperature of 700-800℃, the stop cooling temperature of 300-550℃, and the cooling rate of ≤30℃ / s. At this time, a small amount of ferrite first precipitates along the original austenite grain boundary, and has enough phase transformation time to transform into relatively regular block ferrite, thereby obtaining a small amount of block ferrite (≤10%) without affecting the phase transformation of bainite. As a tough phase, block ferrite can increase the interface area and cause a large plastic deformation at the crack tip, relieve the triaxial tensile stress at the crack tip, and hinder the crack extension; at the same time, the presence of granular bainite inhibits the coordinated deformation of ferrite and increases the deformation resistance. Most cracks need to frequently pass through the interface between bainite and polygonal ferrite during the propagation process. When there is a small proportion of blocky ferrite in the structure, the crack development is effectively inhibited, thus exhibiting better low-temperature DWTT toughness.

[0063] At the same time, a faster cooling rate is conducive to the rapid and uniform transformation of the structure, reducing the segregation of the core structure and the aggregation of inclusions, and avoiding the local hard point defects on the surface, obtaining uniformly refined structure grains in the thickness direction and throughout the plate, ensuring the overall performance of the steel plate is uniform and stable, and ensuring that the steel plate has excellent acid resistance while having good low-temperature toughness.

[0064] Compared with the prior art, the present invention has the following advantages:

[0065] The composition design of the present invention adopts ultra-low C, ultra-low S and low inclusion control, and according to the easy segregation degree of each element and the relationship with the HIC resistance performance, the control requirements of the hydrogen-induced cracking sensitivity coefficient Ks coefficient are proposed to improve the acid resistance of the material. On this basis, Nb+Ti≤0.07%, 0.7≤(Nb+27.5*Ti) / (5C+27*N)≤5.0 are controlled, and the influence of second phase particles such as TiN and NbC on the acid resistance and low-temperature toughness of the material is focused on. At the same time, by adding Cu+Ni+Cr+Mo≤0.80%, the inhibitory effect on block ferrite is reduced, so that a small amount of block ferrite (block ferrite content 3-10%) is contained in the steel structure, and the generation of cracks is inhibited, so that the pipeline steel has better low-temperature toughness on the basis of having higher strength and acid resistance. Conventional acid-resistant pipeline steel has higher contents of C, Mo and Nb elements, and the control of inclusion elements is not considered.

[0066] On the basis of composition design, the present invention adopts DQ+ACC cooling mode in manufacturing process design after rolling, controls the start cooling temperature: 700-800°C, the stop cooling temperature: 300-550°C, the cooling rate ≤30°C / s, appropriately reduces the inhibitory effect of elements such as Mo on blocky ferrite, forms a microstructure of uniform and refined granular bainite + a small amount of blocky ferrite, wherein the blocky ferrite content is 3-10%, the grain size is ≥10 levels, there is no obvious segregation band or hard phase structure, and the blocky ferrite, as a tough phase, can increase the interface area, and cause a large plastic deformation at the crack tip, relieve the triaxial tensile stress at the crack tip, and hinder the crack extension, so that the acid-resistant pipeline steel has good low-temperature toughness. The traditional X60 / X65 grade acid-resistant steel does not contain blocky ferrite.

[0067] The R of the pipeline steel of the present invention t0.5 Yield strength 430~570MPa, tensile strength 520~690MPa, yield strength ratio ≤0.92, A50mm elongation ≥30%, hardness HV10≤220, -49℃ Charpy impact energy ≥400J, -35℃ DWTT SA% ≥90%. The steel plate has excellent acid resistance (no cracking in HIC and SSCC tests (90% SYMS) under international NACE standard A solution), fully meeting the evaluation standards of API 5L. And compared with the existing patents, it has better low-temperature toughness -49℃ Charpy impact energy ≥400J, -35℃ DWTT SA% ≥90%. In conventional acid-resistant pipeline steel, the best low-temperature toughness is -40℃ Charpy impact energy ≥300J, -30℃ DWTT SA% ≥85%. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 It is the scatter plot of HIC crack length rate CLR and coefficient Ks.

[0069] Figure 2 This is a microstructure photograph of the steel according to Example 1 of the present invention. DETAILED DESCRIPTION

[0070] The present invention will be further described below in conjunction with the embodiments and drawings.

[0071] The chemical composition of the steel of the embodiment of the present invention is shown in Table 1 and Table 2, and the balance includes Fe and unavoidable impurities; the specific process parameters are shown in Table 3.

[0072] The mechanical properties and microstructure results of the steel plates of the embodiments of the present invention and the comparative examples are shown in Table 4, and the HIC resistance and SSC resistance results are shown in Table 5.

[0073] Figure 2 This is a microstructure photo of the pipeline steel obtained in Example 1 of the present invention. Figure 1It can be seen that the steel plate obtained by using the composition and process of the present invention has a microstructure of uniformly refined granular bainite and a small amount of blocky ferrite; wherein the content of blocky ferrite is 3-10%, the grain size is ≥10, and there is no obvious segregation band or hard phase structure.

[0074] It can be seen from Table 4 that the R t0.5 The yield strength is 430-570MPa, the tensile strength is 520-690MPa, the yield strength ratio is ≤0.92, the A50mm elongation is ≥30%, the hardness HV10 is ≤220, and it has good low-temperature toughness, the Charpy impact energy at -49℃ is ≥400J, and the DWTT SA% at -35℃ is ≥90%.

[0075] Hydrogen induced cracking (HIC) resistance test: The NACE TM0284-2016 standard "Test method for evaluation of hydrogen induced cracking resistance of steel for pipelines and pressure vessels" was used to measure the hydrogen induced cracking (HIC) resistance in a wet hydrogen sulfide (H2S) environment. The obtained steel was immersed in the standard sample and solution A for 96 hours. The measurement results are shown in Table 5. No cracks appeared in the samples obtained in the embodiments of the present invention.

[0076] Hydrogen sulfide stress corrosion cracking (SSC) resistance test: According to the NACE TM 0177-2016 standard "Test method for resistance of metallic materials to sulfide stress corrosion cracking in pressurized sulfur environments", the hydrogen sulfide stress corrosion cracking (SSC) resistance was measured by using a four-point bending method with a stress loading of 90% SYMS. After 720 hours of immersion in solution A, the measurement results are shown in Table 5. None of the samples of the embodiments of the present invention were broken.

[0077] In the pipeline steel of Comparative Example 1, the C content is relatively high, and Ks reaches 0.311 (the present invention controls Ks≤0.23), (Nb+27.5*Ti) / (5C+27*N) is 0.61 (the present invention controls it within 0.7-5.0), and Cu+Ni+Cr+Mo reaches 0.93% (the present invention controls it within ≤0.80%). Large cracks appear in the HIC test, and two of the three specimens are cracked. The length rate CLR exceeds 20%, and cracks also appear in the SSC test. The DWTT and impact properties are also reduced compared with those of the embodiment.

[0078] In the pipeline steel of Comparative Example 2, the C content is relatively high, and Ks reaches 0.289, the length of the calcium feeding wire is low, the Ca / S ratio is only 1.0 (the present invention controls Ca / S≥2), and the B content reaches 0.0005% (the present invention controls B≤0.0004%), O+N+H reaches 0.0072% (the present invention controls ≤0.0070%), the HIC resistance and toughness are poor, the CLR of one sample reaches 18.56%, cracks also appear in the SSC test, the DWTT is only 70% / 75%, the average impact energy is 279J, and there is a single value of only 208J.

[0079]

[0080]

[0081]

[0082]

[0083]

[0084]

[0085]

Claims

1. A high-toughness X60 / X65 grade acid-resistant pipeline steel, the chemical composition weight percentage of which is: C: 0.015-0.040%, Si: 0.10-0.30%, Mn: 1.18-1.45%, 0<P≤0.008%, 0<S≤0.0010%, Cu: 0.05-0.35%, Ni: 0.05-0.30%, Cr: 0.15-0.30%, Mo: 0.02-0.09%, Nb: 0.025-0.055%, Ti: 0.00 5~0.020%、Ca:0.0010~0.0040%、Alt:0.010~0.040%、0<B≤0.0004%、0<O≤0.0025%、0<N≤0.0050%、0<H≤0.0002%、0<Sn≤0.0050%、0<Sb≤0.0025%、0<Bi≤0.0030%、0<Pb≤0.0050%、0<As≤0.0030%、the balance includes Fe and unavoidable impurities, and at the same time meets: Nb+Ti≤0.07%; Ca / S ≥ 2; Cu+Ni+Cr+Mo≤0.80%; 0<N+O+H≤0.0070%; 0.7≤(Nb+27.5*Ti) / (5C+27*N)≤5.0; Hydrogen induced cracking sensitivity coefficient Ks≤0.23, Ks=8.0C+24S-Alt-2.3Nb+2.8Ti+117B+0.34Ni-0.30Mo+24.5N-0.

19.

2. The high-toughness X60 / X65 grade acid-resistant pipeline steel according to claim 1, characterized in that: The balance is Fe and other inevitable impurities.

3. The high-toughness X60 / X65 grade acid-resistant pipeline steel according to claim 1 or 2, characterized in that: The microstructure of the pipeline steel is uniformly refined granular bainite + a small amount of blocky ferrite, wherein the content of blocky ferrite is 3-10%, the grain size is ≥10, and there is no obvious segregation zone or hard phase structure.

4. The high-toughness X60 / X65 grade acid-resistant pipeline steel according to claim 1, 2 or 3, characterized in that: The R of the pipeline steel t0.5 Yield strength 430~570MPa, tensile strength 520~690MPa, yield strength ratio ≤0.92, A50mm elongation ≥30%, hardness HV10≤220, -49℃ Charpy impact energy ≥400J, -35℃ DWTT SA% ≥90%.

5. The method for manufacturing high-toughness X60 / X65 grade acid-resistant pipeline steel according to any one of claims 1 to 4, characterized in that: The steps include: 1) Hot metal pretreatment Control the S content of hot metal before pretreatment to ≤0.050% and the S content of hot metal entering the furnace to ≤0.0020%; 2) Smelting According to the composition smelting of claim 1 or 2, the C content of the steel is controlled to be ≤0.035%, and the S content of the steel is controlled to be ≤0.0080%; 3) Refining LF and RH refining are used. During LF refining, the stirring time after all alloys are added is controlled to be ≥3min, the RH calcium wire feeding amount is 200-350m, the argon blowing time after the calcium wire feeding is completed is ≥5min, the target Ca content is 10-40ppm, and the Ca / S ratio is controlled to be ≥2; 4) Continuous casting Continuous casting calming time ≥ 3min, superheat controlled at 10~40℃; 5) Reheating Heating temperature: 1100-1200℃, holding time: 200-350min; 6) Controlled rolling Final rolling temperature: 750~900℃; 7) Cooling after rolling Cooling start temperature: 700-800℃, cooling stop temperature: 300-550℃, cooling rate ≤30℃ / s.

6. The manufacturing method according to claim 5, characterized in that: During the smelting process, the bottom blowing flow rate of the converter bottom calming stage is ≥900Nm 3 / h, control the blowing of free oxygen to ≤900ppm.

Citation Information

Patent Citations

  • Steel plate having excellent hydrogen-induced-cracking resistance and toughness, and steel tube for line pipe

    CN105358724A

  • Submarine seamless line pipe above 415SPDF steel grade having large strain resistance

    CN105543690A

  • Low-cost, high-strength and high-toughness X65MS-grade acid-resistant pipeline steel hot-rolled coil plate and preparation method thereof

    CN114107816A

  • Double-resistance pipeline steel plate and production method thereof

    CN116254484A